Ability of Classroom Teachers in Developing Thematic Teaching Materials Based on the 2013 Curriculum - Refta Disriani; Mhmd Habibi; Risna Wati (Journal of Educational Sciences, 2023)
In the learning process, having access to various educational materials is a fundamental necessity. The information needed to understand thematic education can be found in a variety of learning resources. Where the purpose of providing teaching materials is to make the learning process more interesting and easy to learn, With all the basic skills that need to be mastered, the purpose of developing teaching materials is to make the learning process more interesting and easy to learn. Teachers must have the creative abilities and inventiveness needed to produce teaching materials in order to maximize the potential for developing creative teaching materials for thematic learning. The purpose of this study was to determine the ability of grade IV teachers at SD Negeri 004 Teluk Pinang, Gaung Anak Serka District to make thematic teaching materials based on the 2013 curriculum. The type of research presented here is known as quantitative descriptive research. While class IV-A teachers are the topic of this research, the ability of class teachers to produce thematic teaching materials based on the 2013 curriculum is the object of this research. The presentation formula was used in analyzing the data collected for this investigation. Based on the findings, class IV A teachers at SDN 004 Teluk Pinang, Gaung Anak Serka District, were able to develop thematic teaching materials based on the 2013 curriculum; however, teachers do not use teaching materials to facilitate learning in their classrooms. This is supported by observational data, which obtained 70 percent of the total votes and is included in the strong category.